Electrochemical sensors based on carbon composite materials : fabrication, properties and applications - Manjunatha, Jamballi G. (IOP Publishing, 2022)
This book reviews the emerging trends in electrochemical sensors based on carbon composite materials & their applications. Carbon composite materials-based sensors offer elevated sensitivity, selectivity, stability and accuracy compared to other techniques, as well as improved portability through miniaturization. The developed sensors can be applied for routine applications in clinical and industrial settings, as well as in fundamental scientific research as they offer information regarding the mechanism and kinetics of electron transfer reactions occurring at the fabricated electrode surface. The book reviews the emerging research trends and utilization of carbon composite material for electrochemical sensors development for a range of applications in pharmaceutical, industrial, environmental monitoring etc. The focus of this book makes it useful for scientific researchers from the fields of electrochemistry and sensor development that are expected to come together in the newly emerging interdisciplinary research area within electrochemical sensors. Part of IOP Series in Sensors and Sensor Systems.
Keywords: Electrochemical sensors -- Materials.; Carbon composites.; Instruments & instrumentation engineering.; Instrumentation and measurement.; elektronické knihy; electronic books